Effect of 4-META on microtensile bond strength of cements to ceramics - Maliheh Nafisifard; Homayoon Alaghehmand; Laleh Soleimani; Faraneh Mokhtarpour (Wolters Kluwer Medknow Publications, 2024)
Background: This study assessed the effect of different concentrations of 4-methacryloyloxyethy trimellitate anhydride (4-META) added to silane on microtensile bond strength (µTBS) of light-cure and dual-cure resin cement to hybrid and zirconia-reinforced lithium silicate ceramics. Materials and Methods: This in vitro, experimental study was conducted on 32 Celtra Duo and 32 VITA Enamic ceramics bonded to Allcem Veneer light-cure and Allcem dual-cure resin cements using silane impregnated with 4-META in 0%, 2.5%, 5%, and 10 wt% concentrations in 16 groups (n = 4). The µTBS of specimens was measured by a universal testing machine and analyzed by the Kruskal-Wallis and Mann-Whitney tests, and the mode of failure was determined under a stereomicroscope and analyzed by the Chi-square test (alpha = 0.05). Results: The lowest mean µTBS was recorded in the Enamic ceramic group with 4-META (0%) bonded to dual-cure cement (14.26 MPa), and the highest mean µTBS was recorded in Enamic ceramic with 4-META (10%) bonded to light-cure cement (18.59 MPa) (P < 0.001). The µTBS of Celtra Duo was significantly higher than that of Enamic in bonding to light-cure cement using 4-META (2.5%) (P = 0.003). All failures (100%) were adhesive in most groups. The frequency of adhesive failure was the lowest (90%) in Celtra Duo bonded to dual-cure cement with 4-META (5%). Conclusion: According to the results of this pilot study, the addition of 4-META (10%) to silane caused a significant improvement in µTBS to light-cure cement. The addition of 4-META in all concentrations significantly improved the µTBS to Enamic ceramic in the use of dual-cure cement; however, it had no significant effect on µTBS of Celtra Duo. Nonetheless, the results should be interpreted with caution due to the relatively small sample size.